PEMBELAJARAN ALQUR’AN METODE AN NASHR UNTUK MENINGKATKAN KEMAMPUAN BAHASA ANAK USIA DINI DI RA AN NASHR KECAMATAN WAJAK KABUPATEN MALANG - Ifan Nazilatul Badi'ah; Muhammad Hanif; Ika Anggraheni (Jurnal Dewantara, 2022)
Learning the Qur'an needs to be introduced to children from an early age. The method used must be in accordance with the characteristics of early childhood, which is fun and carried out repeatedly. The method of learning the Qur’an An Nashr according to the needs of the child is carried out repeatedly, read part of mufrodat and the child can understand its meaning. Qualitative research methods with the type of case studies are very appropriate to describe the implementation, stages and effectiveness of the An Nashr method. The research was carried out at RA Nashr, Wajak District, Malang Regency. The results of the study, namely the An Nashr method, can improve children's Memorization of the Qur'an, language and cognitive abilities of early childhood